VIRUSES OF MARINE MAMMALS AND METAGENOMIC MONITORING OF INFECTIOUS DISEASES - A. I. Kydyrmanov; K. O. Karamendin (Scientific Journal of Pedagogy and Economics, 2019)
The review presents information on epizootic diseases in marine mammals caused by influenza viruses of genera A and B, morbilliviruses, adeno-, herpes-, calici- and coronoviruses. Virological and serological data about the spectrum of viral infections in marine mammals are given. Describes epizootic events in marine mammals induced by influenza A viruses and isolation of strains with antigenic formulas H1N1, H1N3, H3N3, H3N8, H4N5, H4N6, H7N7, H10N7, H13N2, H13N9. It is suggested that the seals may be infected with a wide range of influenza viruses by direct transmission without prior adaptation. It is emphasized that marine pinnipeds can serve as one of the reservoirs of human influenza B virus in nature. Data on the classification of pinniped and cetacean coronaviruses are presented. A variety of pinnipeds herpesviruses and the clinical significance of their morbidity indicators in the diagnosis of viral infections of seals are shown. It emphasizes the need for the development of proactive diagnostic tools for the timely detection of new viruses with zoonotic potential that can cause disease outbreaks. The negative effects of diseases with unknown etiologies on the population of Caspian seals are noted. The conclusion is made about the need for metagenomic monitoring of Caspian seal virome in order to establish the role of viral pathogens in their morbidity and regular mortality under conditions of intensive habitat development.